Improved Fixed-Time Attitude Tracking Control for Quadcopter Unmanned Aerial Vehicles - Xuan Nguyen; Sun Myung Won; Truong Dong do; Sung Kyung Hong (IEEE Access)
Quadcopters have become a unmanned aerial vehicle class playing essential roles in a wide range of real-world applications. Many missions in such applications require the quadcopter’s attitude to converge to given setpoints in a fixed time. However, existing controllers deliver fixed-time convergence at a high cost of energy consumption. This paper presents a fixed-time quadcopter attitude controller, which advances existing quadcopter control algorithms in terms of convergence speed and energy consumption. First, the quadcopter dynamics is presented. Second, based on the dynamical model, an improved fixed-time sliding mode controller is proposed. Next, the fixed-time convergence and stability of the closed-loop system are strictly analyzed by using the Lyapunov theory. Additionally, numerical simulations are conducted to verify the feasibility and efficacy of the proposed method. Through comparisons with closely related works, the effectiveness of our algorithm is emphasized. Finally, experimental results demonstrate the feasibility and applicability of our work in real-world systems.